Predictors of mortality in newborns with esophageal atresia: a 6-year study in a single institution - Leecarlo Milano; Nunik Agustriani; Rochadi Rochadi (Indonesian Pediatric Society, 2015)
Background Esophageal atresia, with or without fistula, is a congenital defect that causes high morbidity and mortality in newborns. Risk factors of mortality need to be identified to establish the best approach for treating this condition in order to decrease morbidity and mortality.Objective To identify factors associated with mortality in newborns with oesophageal atresia.Methods We reviewed all newborns with esophageal atresia using data from their medical records at Sardjito General Hospital from January 2007 to December 2012. Potential risk factors were analyzed using Chi-square test, with a level of significance of P<0.05.Results Of 31 newborns that met our criteria, only 5 survived, and all 5 had one-stage surgery (primary anastomosis with fistula ligation). Thrombocytopenia and sepsis increased the risk of death with OR 10.857 (95%CI 1.029 to 114.578) and OR 13.333 (95% CI 1.242 to 143.151), respectively. However, anemia had a protective effect against mortality with OR 0.688 (95%CI 0.494 to 0.957).Conclusion Thrombocytopenia and sepsis are the risk factors associated with mortality in newborns with esophageal atresia at our institution. Anemia has a protective effect against mortality.